Missing persons : a Private novel [large type] - Patterson, James, 1947-; Hamdy, Adam, 1974- (Patterson, James, 1947- Private novels, 2024)
In Afghanistan, a US pilot is shot down during a covert mission. In New York, a mother is forced to flee with her two young children. Finding the connection between the two will lead the Private team right into a deadly trap.